HPB O07 Complication profile of laparoscopic common bile duct exploration: Results from R-ALiCE Study. (7th December 2022) - Tanase, Andrei; Aroori, Somaiah; Dhanda, Ashwin; Cramp, Matthew; Streeter, Adam; ,
Abstract: Background: There are two ways of managing common bile duct stones (CBDS); a two-stage and a single-stage approach. The two-stage procedure is the most common way of managing CBDS in the UK. In the two-stage approach, patients have pre-operative confirmation of CBDS followed by endoscopic retrograde cholangio pancreatography (ERCP) and delayed cholecystectomy. The single-stage approach is an equally effective but less favoured approach, which involves simultaneous intra-operative imaging followed by laparoscopic CBD exploration and cholecystectomy. Evidence supports that the single-stage approach is associated with reduced costs, length of stay, and better stone-free survival compared to the two-stage approach. Despite the evidence favouring the single-stage approach, it is still not widely used, and one of the reasons for this could be the lack of complication profile data from extensive multi-centre studies. We undertook a large multi-centre study called R-ALiCE (Retrospective- Audit of Laparoscopic Common Bile duct Exploration). One of the study's aims was to evaluate the outcome profile of LCBDE in the UK. Methods: R-ALiCE Study was a multi-centre collaborative cohort study that collected data on all LCBDEs performed over five years (2015–2019) in 18 centres across the UK. A total of 1796 patients were enrolled on the study, and 1689 patients were included in the final analysis. The reasons for exclusion of 107 patients were: incomplete data: 13, open surgery: 11, LCBDE was not performed: 55, young adult=1, and 27 patients outside the time frame. Results: The median age of patients (68.2% females) was 59 years (interquartile range: 43–71). One-third of patients had underlying cardiovascular co-morbidities, 14.6% had respiratory co-morbidities, and 3.1% had underlying liver disease. Almost 50% were obese (body mass index), and 28.2% were overweight. Fifty-six percent of (945) patients had an emergency/semi-elective procedure, while 44% (743) had an elective procedure. The median surgery duration was 123.9 minutes (range: 29–420). Laparoscopic to open conversion rate was 5%. Transcystic-exploration (TC-LCBDE) was attempted in 71.6% of all cases with a success rate of 77.6%. Transcholedochal-exploration (TD-LCBDE) was attempted in 41.1% of all cases: 12.5% were TC-LCBDE progressed to TD-LCBDE and 28.3% were direct TD-LCBDE. Overall, 30-day all-cause complication rate was 18.9% (319). Complication rate between TC and TD were: bile leak rate was 1.4% vs. 8.8% (p=0.000), retained stones 4.9% vs 5.6%(p=0.527), pancreatitis (0.9% vs 1% (p=0.828) and intrabdominal collections 1.8% vs 7.2%. Thirty-five percent of bile leaks were Grade A and 39% Grade B. The overall complication rate was 12.8% for TC and 27.7% for TD. Overall 30-day mortality was zero. Conclusions: This is the largest LCBDE cohort study in the world and confirms that overall complications of LCBDE are low, and LCBDE can be safely performed for patients with simultaneous gallstones and bile duct stones. Transcystic approach should always be attempted as first line in selected patients to reduce the risk of complications.